PENINGKATAN AKTIVITAS DAN HASIL BELAJAR PEMBELAJARAN MATEMATIKA MENGGUNAKAN MEDIA MANIPULATIF DI SEKOLAH DASAR - Noeryauni, Andi; Margiati, K.Y.; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to describe the increase in activities and learning outcomes of students in learning by using analogue manipulative media in class V Elementary School 9 Pontianak Barat. This form of research is a classroom action research with the subject of research teachers and students VD class of 37 people. The method used is descriptive method. Data collection techniques used are direct observation techniques, document scrutiny techniques with data collection instruments are observation sheets and formative test questions. Data analysis techniques used are calculate the average and percentage. This research is done as much as II cycle and every cycle consist of 3 meetings with result obtained are: 1) the ability of teacher to design learning starting from cycle I that is 3,62 and cycle II is 3,81; 2) the ability of teachers to implement the learning cycle I is 3.27 and cycle II is 3.88; 3) Student learning activity in cycle I is 65,94%, cycle II that is 76,22%; 4) Student learning outcomes in cycle I of 78.94 and cycle II equal to 86.86. From the data obtained shows that by using manipulative media can increase student activity and learning outcomes in class V Elementary School 9 Pontianak Barat.Â Keywords: Improvement, Activity, Learning Outcomes, Manipulative Media, Mathematics Learning